PEMILIHAN E-MARKETPLACE BAGI PEDAGANG BATIK PEKALONGAN MENGGUNAKAN METODE FUZZY AHP-TOPSIS - Nur Ika Royanti; Era Yunianto (Universitas Muhammadiyah Semarang, 2018)
Nowadays Pekalongan batik traders have adopted electronic marketing using e- marketplace. The quality of an e-marketplace affects the number of customers who decide to shop through the e-marketplace. Dimensions that affect the quality of an e-marketplace include service quality, system quality, information quality and vendor-specific quality. In this study, the e-marketplace for Pekalongan batik traders will be chosen as an effort to expand market access using the integration of fuzzy AHP and fuzzy TOPSIS methods. In collecting data using a questionnaire given to Pekalongan batik traders. The results of the study showed that the service quality criteria had a weight of 28.4%, the system quality criteria had a weight of 23.1%, the information quality criteria had a weight of 25.1% and the vendor specific quality criteria had a weight of 23.4%. Alternate ranking sequences are TP (CC 0.7543), LAZ (CC 0.07535) and BL (CC 0.07281). The results of this study are expected to be a recommendation for Pekalongan batik traders in the selection of e-marketplace as a market expansion effort and for e-marketplace developers in determining e- marketplace development strategies Keywords: Fuzzy AHP, Fuzzy TOPSIS, e-marketplace